Jenang Grendul Sebagai Simbol Bulan Safar di Dusun Banjar Patoman, Amadanom, Dampit, Kabupaten Malang - Abdul Qodir Abdillah (ICODEV: Indonesian Community Development Journal, 2022)
Jenang grendul is one of the traditional foods in Indonesia. Traditional foods which is part of culture, including foods, drinks or snacks that are traditionally made and consumed, also have developed for a long time, specifically in a certain area in Indonesia. Jenang grendul only made in the month of Safar in Banjar Patoman, Amadanom, Sub-districts of Dampit. The aim of this research is to determine the philosophy of jenang grendul and its relation to the month of Safar. This research is a field research, which is the result is collected by interviewing people around and then supported by some literature. Based on the data obtained, the philosophy of jenang grendul is associated with the story of the Prophet Musa as, especially when King Fir'aun and his troops are drowned. King Fir'aun and his troops were symbolized by grendul and the drowning sea water was symbolized by the jenang sauce. The other information also states that the philosophy of jenang grendul is associated with the warning of thousands of bala' (unlucky days), which sent down by Allah SWT. Both events have occurred in the month of Safar, therefore jenang grendul made in that month as a symbol.